The Role of Artificial Intelligence in Enhancing Efficiency, Transparency, and Inclusivity of Public Services in Indonesia: Opportunities, Challenges, and Strategic Approaches - Chairuddin, Andy; Rifdan, Rifdan; Ilyas, Asmiana Saputri; Mustari, Sahdan; Suprianto, Suprianto; Rizaputra, Rizaputra (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Artificial intelligence (AI) is a technology with immense potential to enhance public service efficiency, transparency, and inclusivity. This study aims to explore the role of AI in improving the efficiency of public services in Indonesia and to identify the supporting and hindering factors in its implementation. A descriptive qualitative approach was employed, focusing on major cities like Jakarta and Surabaya and remote areas facing challenges in digital transformation. The findings reveal that AI has successfully improved efficiency in urban areas, particularly in managing civil registration documents and transportation systems. However, implementing AI remains hindered by infrastructure limitations, low digital literacy, algorithmic bias risks, lack of transparency, and concerns regarding data security and privacy, especially in remote regions. This study also highlights that inclusive and ethical AI implementation is crucial to ensuring the benefits of this technology are equitably distributed. Strategic measures such as digital infrastructure development, improving digital literacy, and establishing robust regulations are necessary for AI to become a significant transformative tool in creating more efficient and equitable public services.